Diurnal butterflies of the Serranía de los Churumbelas, Cauca. Altitudinal distribution and species diversity (Lepidoptera: Rhopalocera: Papilionoidea) - ARIAS-B., JOHN JAIRO; HUERTAS-H., BLANCA C. (Revista Colombiana de Entomología, 2001)
The role of the butterflies as indicators of endemism biodiversity extend of forest intervention and forest quality and surveys of this group are of great importance to the conservation of pristine forest siles such as Serranía de Los Churumbeles, department of Cauca. We present an inventory of diurnal butterflies collected by the Colombia'98 expedition. The adults were collected an altitudinal gradient from 350-1450 m. and include information on biology, abundance, and elevational distribution patterns of species. A total of 144 species were recorded in five families and 12 subfamilies. The highest levels of diversity were recorded at 350 and 700 m elevations, and the largest diversity was at 1450 m. We noticed that as we went higher in altitude we recorded at a greater number of butterflies; which means that the lower the altitude the less similarity in the species. The high levels of diversity recorded at these altitudes are probably due to highly variable vegetation and biogeographical resources. The Serranía de Los Churumbeles is an important site for future conservation, due to its highly diverse Lepidoptera fauna which includes many rare or poorly known species with few specimens in collections, which demonstrate the pristine characters of the forest in the region, despite the presence of some forest border species.